2020
DOI: 10.1021/jasms.0c00234
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Epitope and Affinity Determination of the Myocardial Infarction Marker Myoglobin by SPR-Biosensor Mass Spectrometry

Abstract: Myoglobin (MG) is a biomarker for heart muscle injury, making it a potential target protein for early detection of myocardial infarction. Elevated myoglobin levels alone have low specificity for acute myocardial infarction (AMI) but in combination with cardiac troponin T have been considered highly efficient diagnostic biomarkers. Myoglobin is a monomeric heme protein with a molecular weight of 17 kDa that is found in skeletal and cardiac tissue as an intracellular storage unit of oxygen. MG consists of eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…The proteolytic epitope extraction-MS approach has been successfully applied to a number of epitope identifications of monoclonal, as well as polyclonal antibodies [ 6 , 7 , 38 ]. Two antibody immobilization methods were explored: (i), random immobilization on activated surface-assembled monolayer (SAM) chips; and (ii), oriented antibody immobilization using the F c binding of protein G [ 38 ] ( Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The proteolytic epitope extraction-MS approach has been successfully applied to a number of epitope identifications of monoclonal, as well as polyclonal antibodies [ 6 , 7 , 38 ]. Two antibody immobilization methods were explored: (i), random immobilization on activated surface-assembled monolayer (SAM) chips; and (ii), oriented antibody immobilization using the F c binding of protein G [ 38 ] ( Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The proteolytic epitope extraction-MS approach has been successfully applied to a number of epitope identifications of monoclonal, as well as polyclonal antibodies [ 6 , 7 , 38 ]. Two antibody immobilization methods were explored: (i), random immobilization on activated surface-assembled monolayer (SAM) chips; and (ii), oriented antibody immobilization using the F c binding of protein G [ 38 ] ( Figure S3 ). The comparison of both methods clearly showed that immobilization using covalent crosslinking at the Fc region to protein G was superior to standard immobilization with regard to long-term antibody stabilities; reproducibility; antibody consumption for immobilization; and non-specific binding to the surface [ 32 , 38 ] ( Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations